Bioethanol production from coconut husk using DES-NADES pretreatment and enzymatic hydrolysis method - Yerizam, Muhammad; Jannah, Asyeni Miftahul; Aprianti, Nabila; Yandriani, Yandriani; Rendana, Muhammad; Ernas, Annisa Qonita; Tamba, Juice Lowise (Comptes Rendus. Chimie)
Bioethanol is an alternative fuel produced during biomass fermentation. Among the available biomass resources for bioethanol production, coconut husk is an interesting raw material due to its high cellulose content. This study aims to evaluate the coconut husk conversion into bioethanol using DES (ChCl:MEA) and NADES (Be:La) solvents for the delignification process. The molar ratios of HBA and HBD of the two solvents were varied (1:4, 1:6, 1:8) at 2, 4, 6, and 8 h for each ratio. The delignified samples were hydrolyzed using the 5% (w/w) of cellulase enzymes and fermented for seven days using Saccharomyces cerevisiae. The results showed that DES (ChCl:MEA) and NADES (Be:La) could remove lignin at about 60.53% and 65.81%. The glucose content was obtained at 0.5% (brix) by both solvents and bioethanol content was obtained at 13.9% and 14% (v/v) for DES and NADES, respectively.